Epilepsy, anti-seizure medication, intellectual disability and challenging behaviour – Everyone's business, no one's priority. (October 2020) - Kinney, M.O.; Chester, V.; Tromans, S.; Alexander, R.T; Angus-Leppan, H.; Bagary, M.; Cock, H.; Devapriam, J.; Hassiotis, A.; Mula, M.; Reuber, M.; Ring, H.; et al.
Highlights: Epilepsy in Intellectual Disability is managed by different professional groups A common presentation is behaviour change related to epilepsy related drug changes Little is known on how different groups approach concerns of challenging behaviour Study examines training status, confidence and management practices across groups There is considerable diagnostic overshadowing & need for training between groups Abstract: Purpose: People with Intellectual Disability (ID) and epilepsy are more likely to experience psychiatric conditions, challenging behaviour (CB), treatment resistance and adverse effects of anti-seizure medications (ASM) than those without. This population receives care from various professionals, depending on local care pathways. This study evaluates the training status, confidence, reported assessment and management practices of different professional groups involved in caring for people with ID, epilepsy and CB. Methods: A cross sectional survey using a questionnaire developed by expert consensus which measured self-reported training status, confidence, and approaches to assessment and management of CB in people with ID and epilepsy was distributed to practitioners involved in epilepsy and/or ID. Results: Of the 83 respondents, the majority had either a psychiatry/ID (n = 39), or Neurology/epileptology background (n = 31). Psychiatry/ID and Neurology/epileptology had similar confidence in assessing CB in ID-epilepsy cases, but Psychiatry/ID exhibited higher self-rated confidence in the management of these cases. While assessing and managing CB, Psychiatry/ID appeared more likely to consider mental health aspects, while Neurology/epileptology typically focused on ASM. Conclusion: Psychiatry/ID and Neurology/epileptology professionals had varying training levels in epilepsy, ID and CB, had differing confidence levels in managing this patient population, and considered different factors when approaching assessment and management. As such, training opportunities in ID should be offered to neurology professionals, and vice versa. Based on the findings, a best practice checklist is presented, which aims to provide clinicians with a structured framework to consider causal explanations for CB in this population.